A new species of Parianella (Poaceae, Bambusoideae, Olyreae) marks the southernmost distribution of the genus in Brazil - Ferreira, Fabrício Moreira; Oliveira, Reyjane P.; Clark, Lynn G.; Welker, Cassiano A. Dorneles (Plant ecology and evolution, 2022)
Background and aims – Parianella is a relatively recently described genus of the subtribe Parianinae (Poaceae, Bambusoideae, Olyreae) that includes two species, and it is supposedly endemic to the Bahian Coastal Forests in the central region of Atlantic Forest, Brazil. Herein, we describe and illustrate a new species of the genus, comparing it with the other species of Parianella . We also provide an updated distribution map of the genus and the conservation status of the new taxon. Material and methods – This study was based on the analysis of herbarium specimens and a literature review. The conservation assessment is based on field observations and spatial analyses, following IUCN guidelines and criteria. Key results – During a review of the Poaceae collection of the MBML Herbarium, two Parianinae specimens with interesting features were found. A detailed morphological analysis revealed that these specimens belong to a new species of Parianella . The new taxon was collected in two localities in the southern portion of the Brazilian state of Espírito Santo, one in the municipality of Santa Leopoldina and the other in the Duas Bocas Biological Reserve, municipality of Cariacica. Both localities are situated in the Krenák-Waitaká Forests, one of the three subregions of the central Atlantic Forest region, and an area of great floristic diversity, including bamboo species. Conclusion – Parianella capixaba represents the southernmost distribution of the genus known to date. With the description of this new species, the total number of bamboos in Espírito Santo state rises to 52 species in 18 genera.